Employing Wordvice Artificial Intelligence to Instruct on English Subject-Verb Agreement - Jundy Mardhatillah (Journal of Innovation in English Education and Language Teaching, 2025)
Subject-Verb Agreement in English is a fundamental aspect of grammar that must be learned in the English Department at UIN Ar-Raniry Banda Aceh. One of the media that can be used as an assistant to instruct on English subject-verb agreement is using artificial intelligence. The objective of this study is to ascertain if it can influence students' learning results. This research employed a quantitative approach utilizing a pre-experimental design. The sample comprised 22 students from an intermediate grammar class, from a total population of 183 in batch 23. Data gathering employed pre- and post-assessments. The researcher utilized SPSS Version 27.0 for data processing. The findings indicated that the use of Wordvice artificial intelligence influenced grammar instruction and students' learning outcomes. The students' pre-test mean score was 33.64, with a standard deviation of 15.975, whereas the post-test mean score was 53.41, accompanied by a standard deviation of 17.48.